Pendidikan Life Skill Berbasis Gender - Ramadona, Nurhappy (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2023)
This research reviews how the application of skill life education gender-specific madrasah extracurricular activities at MAS Al-Ishlahiyah Binjai. This study aims to determine the type, direction, objectives and management as well as evaluation of the implementation of gender-specific madrasah extracurricular activities at the madrasah. This research data is qualitative type with descriptive survey technique. The research instruments are direct observation by the author and interview guidelines. The data source of this research is the results of interviews with madrasah alumni who are fairly active in extracurricular activities in madrasah and the author's experience when taking levels in madrasah. The result of this research is that the implementation and improvement of women's extracurricular activities must be carried out in every educational institution without gender bias. The implementation process is carried out by the head of the madrasa and vice madrasa as well as teachers with a deft attitude in determining various extracurricular activities without discriminating between male and female students. The impact and implications of this research are for students to be able to make a means of developing talents and interests and increasing the potential of students in the madrasah environment. Meanwhile, teachers can pay attention to things that support and influence intelligence in children. Abstrak Penelitian ini menyelidiki tentang bagaimana pengaplikasian pendidikan life skill berbasis gender terutama pada kegiatan ekstrakurikuler madrasah yang berspektif gender di MAS Al-Ishlahiyah Binjai. Penelitian ini bertujuan untuk mengetahui jenis, arah, sasaran dan pengelolaan serta evaluasi pelaksanaan ekstrakurikuler madrasah berspektif gender di madrasah tersebut. Data penelitian ini berjenis kualitatif dengan teknik survey deksriptif. Adapun instrumen penelitiannya adalah observasi langsung oleh penulis dan pedoman wawancara. Sumber data penelitian ini adalah hasil wawancara kepada alumni madrasah yang terbilang aktif dalam ekstrakurikuler madrasah dan pengalaman penulis ketika menempuh jenjang di madrasah. Hasil dari penelitian ini adalah implementation and improvement serta inovasi pada visi dan misi ekstrakurikuler khusus perempuan harus dijalankan di setiap instansi pendidikan tanpa adanya bias gender. Proses pelaksanaannya dilakukan oleh kepala madrasah dan wakil madrsah serta guru dengan sikap cekatan dalam menentukan berbagai kegiatan ekstrakurikuler tanpa membeda-bedakan antara siswa laki-laki dan siswi perempuan. Adapun dampak dan implikasi dari penelitian ini adalah bagi peserta didik dapat menjadikan sarana dalam mengembangkan bakat dan minat serta menambah potensi peserta didik di lingkungan madrasah. Sedangkan bagi guru dapat memperhatikan suatu hal yang mendukung dan mempengaruhi kecerdasan pada anak.